Sphaeropsis sapinea and Associated Endophytes in Scots Pine: Interactions and Effect on the Host Under Variable Water Content - Blumenstein, Kathrin; Bußkamp, Johanna; Langer, Gitta Jutta; Schlößer, Rebekka; Parra Rojas, Natalia Marion; Terhonen, Eeva (Frontiers in Forests and Global Change, 2021)
The ascomycete Sphaeropsis sapinea is the causal agent of the Diplodia Tip Blight disease on pines and other conifer species. This fungus has a symptomless endophytic life stage. Disease symptoms come visible when trees have been weakened by abiotic stress, usually related to warmer temperature and drought. Nowadays, this disease is observed regularly in Scots pine (Pinus sylvestris) sites in parts of Europe, such as Germany, increasing dramatically in the last decade. Changes in climatic conditions will gradually increase the damages caused by that fungus, because it is favored by elevated temperature. Thus, the host trees with reduced vitality due to climate-change related environmental stress are expected to be more susceptible for a Diplodia Tip Blight disease outbreak. There is currently no established and effective method to control S. sapinea. This project aims to reveal the nature of the endophyte community of Scots pine. Utilizing the antagonistic core community of endophytes could serve as novel tool for disease control. Results from this study can serve as a starting point for new solutions to improve forest health against S. sapinea disease outbreaks. We screened potential antagonistic endophytes against S. sapinea and infected Scots pine seedlings with the most common endophytes and S. sapinea by single and combination infections. The stress of the host was increased with low water contents. The antagonism study revealed 13 possible fungi with the capability to inhibit the growth of S. sapinea in vitro, for example Sydowia polyspora. None of the tested co-infected fungi (Desmazierella acicola, Didymellaceae sp. Microsphaeropsis olivacea, S. polyspora, and Truncatella conorum-piceae) showed strong necrosis development in vivo, even when host stress increased due to drought. However, the infection experiment demonstrated the enhancing effect of drought conditions on the disease outbreak, by triggering S. sapinea to cause higher necrosis in the infected twigs.